Three case reports of collagenous gastritis in children: Lessons for an endoscopic and histologic approach to mucosal nodularity of the stomach. Issue 11 (March 2019) - Lee, Yeoun Joo; Lee, Mijeong; Kim, Dae-joong; Lee, Seungkoo; Hong, Jeana
Abstract: Rationale: Collagenous gastritis (CG) is a rare form of chronic gastritis defined histologically by a thickened subepithelial collageneous band in the lamina propria. However, the clinical features and endoscopic findings of CG have not been clearly established in the pediatric population. Presenting concerns: We report the cases of 3 children who presented with intractable anemia and minimal or no gastrointestinal (GI) symptoms and were followed up without definitive diagnosis determination even through diagnostic endoscopic evaluations. Diagnoses: On repeated endoscopic examination, we determined thickened subepithelial collagen band, confirmed by Masson trichrome staining using targeted biopsies of the intervening mucosa between the prominent nodular lesions. Interventions: Under the diagnosis of CG, a course of steroid was administrated in 1 patient, while all patients continued oral iron replacement therapy. Outcomes: All 3 patients remained asymptomatic and their anemia was alleviated with continued administration of oral iron. Main lessons: We recommend early endoscopic evaluation for patients with unexplained anemia, emphasizing a high index of suspicion for CG, despite the absence of definitive GI symptoms. Targeted gastric biopsies should be performed in the depressed mucosa surrounding the nodules, as well as the nodules themselves, to confirm CG, when presented with nodular gastric mucosa in endoscopy.